Copper, brass, and bronze surfaces : a guide to alloys, finishes, fabrication and maintenance in architecture and art - Zahner, L. William (Zahner's architectural metals series, 2020)
"Copper, Brass, and Bronze, the third book in Zahner's Architectural Metals Series, is a comprehensive and authoritative treatment of copper, brass, and bronze applications in architecture and art. This visual, full-color guide offers architecture and design professionals the information they need to ensure proper maintenance and fabrication techniques. Zahner's approach to the use of copper, brass, and bronze in architecture and art covers everything from the history of the metals and choosing the right alloy, to detailed information on a variety of surface and chemical finishes and corrosion resistance. Case studies offer architecture and design professionals strategies for designing and executing successful projects using copper, brass, and bronze. About the series: Zahner's Architectural Metals Series offers in-depth coverage of today's most commonly used metals in architecture and art. These heavily illustrated guides offer comprehensive coverage of how each metal is used in creating surfaces for building exteriors, interiors, and art finishes. Volumes in the series cover: Stainless Steel; Aluminum; Copper, Brass and Bronze; Steels; and Zinc"--